Pengaruh Stres Kerja dan Beban Kerja Terhadap Kinerja Karyawan di UPTD Puskesmas Salawu Kabupaten Tasikmalaya - Rizky Muhammad Purnama; Aditia Abdurachman (Jurnal Publikasi Sistem Informasi dan Manajemen Bisnis, 2026)
Community health center staff performance is crucial to the provision of high-quality health services, as stated in Law 6 of 2023 and Minister of Health Regulation 19 of 2024. Central Statistics Agency (2026) statistics and prior research on health workers both point to the possibility that high workloads and stress on the job impact employee performance. Service quality at the UPTD Salawu Community Health Center in Tasikmalaya Regency is susceptible to factors such as staff burnout, excessive workloads, and unsupportive work environments. Furthermore, there are still gaps in the literature and contradictory results when it comes to studying the correlation between stress on the job, workload, and productivity. Consequently, the purpose of this research is to examine how stress and workload at UPTD Salawu Community Health Center in Tasikmalaya Regency affect workers' productivity. This study employed a quantitative approach based on a survey methodology, with 99 employees receiving questionnaires. Saturated sampling techniques were utilised to choose all employees as samples. Workload and stress at work have a favourable effect on productivity, according to the findings. Maintaining a manageable level of stress at work enhances concentration, self-control, and accountability; distributing responsibilities fairly boosts output and the standard of care for the community.